The effects of 2-methoxy-1,4-naphthoquinone (mnq) on glucose metabolism of mda-mb-231 cells - Daud, Syukriyah Mat (2020)
Quinone and its derivatives are shown to have biological activities and medicinal properties including antibacterial, antifungal as well as anticancer activities. To date, the researchers have been focusing on targeting the chemotherapeutic drugs at the specific genes or proteins/enzymes of cancer metabolism. In this study, 2-Methoxy-1,4- Naphthoquinone (MNQ) was selected based on the increasing reports of its medicinal effects in promoting cancer cells death. The aim of this study is to evaluate the effects of MNQ on glucose metabolism in triple-negative breast cancer, MDA-MB-231 cells. Initially, the MDA-MB-231 cells were treated with various doses of MNQ to determine the growth inhibitory effects and the IC50 dose. The effect of MNQ on cell growth was also tested in non-malignant breast epithelial cells, MCF10A. For further analyses, the cells were treated with IC50 dose of MNQ for measurement of glucose uptake, lactate production as well as the expression of glycolysis-related molecules (GLUT1, Akt, HKII and HIF1). The effect of MNQ was also tested on the autophagy activities and the expression of autophagy-related genes (Beclin 1 and LC3). The results showed that MNQ inhibited the proliferation of MDA-MB-231cells with IC₅₀ values of 43, 29 and 22 μM (24, 48 and 72 h of treatment) but not in MCF10A cells. MNQ also inhibited the glycolytic activities in MDA-MB-231 cells by inhibiting the glucose uptake and reducing the lactate production. The down-regulation of GLUT1 and Akt in both gene and protein expression of MDA-MB-231 cells suggested that inhibition of gycolysis by MNQ was mediated by GLUT1/Akt signaling pathways. Increased HKII, Beclin 1 and LC3 gene expression as well as the formation of autophagosomes in MDA-MB-231 cells showed that MNQ induced the autophagy activity. The inhibition of glucose uptake into the cells may cause the nutrient deprivation and lead to the activation of autophagy in MDA-MB-231 cells. In conclusion, the ability of MNQ to inhibit glycolysis by targeting the glycolysis-related molecules in triple-negative breast cancer cells (MDAMB- 231), indicated the potential of MNQ as anticancer agent/adjuvant in breast cancer treatment.